The Effect of Board Characteristics on Firm Performance with Intellectual Capital as a Moderating Variable: (An Empirical Study of Conventional Commercial Bank Companies on the Indonesia Stock Exchange in 2019–2023) - Hepy Wijayanti; Susi Sarumpaet (International Journal of Economics, Management and Accounting, 2025)
In the traditional commercial banking industry, this study attempts to provide empirical data about the impact of board size and gender diversity on business performance, using intellectual capital as a moderating variable. The research population includes all companies in the conventional commercial bank sector as many as 39 companies, with purposive sampling technique resulting in 36 companies as samples. The analysis methods used include descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and moderation regression analysis. Multiple linear regression results demonstrate that board size significantly and favourably affects business success, while gender diversity has no significant effect. In addition, moderation regression analysis results demonstrate that intellectual capital can fortify the relationship between board size and company performance, but does not strengthen the connection between business performance and gender diversity.